Combined maternal KIR2DL4 and fetal HLA-G polymorphisms were associated with preeclampsia in a Han Chinese population - Ma, Yantuanjin; Qian, Yuan; Jiang, Hong; Meng, Haiyun; Wang, Yang; Yang, Yuling (Frontiers in Genetics, 2024)
Preeclampsia is the main cause of maternal and infant mortality and morbidity during pregnancy. Killer cell immunoglobulin-like receptor 2DL4 (KIR2DL4) and human leukocyte antigen G (HLA-G) play crucial roles in immune tolerance at the maternalfetal interface. In this case-control study, 154 maternal-fetal pairs were recruited, including 74 pairs with preeclampsia (56 of 74 pairs from family triads) and 80 pairs with a normal pregnancy (78 of 80 pairs from family triads). SNaPshot technology was used to detect genetic polymorphisms for 7 TagSNPs in the KIR2DL4 and HLA-G genes. Among the fetal HLA-G gene polymorphisms, rs9380142 (A vs. G: OR=2.802, 95% CI=1.761-4.458) and rs1063320 (G vs. C: OR= 1.807, 95% CI=1.144-2.852) differed between the preeclampsia group and the control group. The transmission disequilibrium test (TDT) suggested that the differences in the rs9380142 G/A polymorphism in foetuses between preeclampsia triads and control triads were due to differences in transmission from the parents (P = 0.001). There was no significant difference in the distribution of maternal KIR2DL4 alleles or genotype frequency between the preeclampsia group and the control group. Gene-gene interaction analysis revealed that the combined genotypes of maternal rs649216-CC and fetal rs9380142-GG, maternal rs1051456-CG/GG and fetal rs9380142-GG, maternal rs34785252-CC and fetal rs9380142-AA/GA, and maternal rs34785252-CC/AA and fetal rs9380142-GG were associated with a significantly lower risk of preeclampsia. Therefore, this study suggested that the combination of maternal KIR2DL4 and fetal HLA-G polymorphisms was associated with preeclampsia in a Han Chinese population.